Reasons for Weak Reading Skills in English among Elementary School Students from the Perspective of English Teachers in Elementary Schools in Riyadh - Aljurijeer, Shamma Sulimsn (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to analyze the underlying reasons behind weak English reading skills among elementary school students, explore manifestations of this weakness, and propose solutions to improve the current situation from the perspective of English teachers in elementary schools in Riyadh. The study adopted a descriptive-analytical approach, collecting data from 240 English teachers in Riyadh’s elementary schools using a questionnaire, The findings revealed several factors contributing to weak reading skills, including lack of teacher engagement, insufficient educational support, ineffective teaching strategies, and curriculum-related challenges. Manifestations of reading weakness included difficulty in pronunciation, avoidance of reading, and lack of interest in studying, Based on the results, the researcher recommended fostering a more encouraging and interactive educational environment, improving reading instruction methods to motivate students, and updating curricula to better meet students' educational needs. The study aims to provide practical solutions to enhance educational quality and strengthen students' abilities, highlighting its significance in improving English reading skills.
Keywords: Reading skill; English language; Education; Primary stage; Saudi Arabia